Women's Empowerment Strategy Towards Gender Equality as an Effort to Encourage The Success of The SDGs in The 3T Region - Ngabito, Dewi; Ibrahim, Rizkyanto; Sholehah, Nur Lazimatul Hilma (Publik : (Jurnal Ilmu Administrasi), 2025)
Sustainable development in 3T (Disadvantaged, Frontier, Outermost) areas faces multidimensional challenges in realising gender equality. Conceptually, women's empowerment in disadvantaged areas requires a holistic approach that considers geographical, cultural, and structural aspects. In the policy context, various empowerment programmes so far still face obstacles in terms of effectiveness and sustainability. This study aims to analyze women's empowerment strategies in achieving gender equality as an effort to support the success of the Sustainable Development Goals (SDGs) in the 3T region. The urgency of this research stems from the fact that women in the 3T region face more complex challenges than those in other regions, including limited access to education, health services, and economic opportunities, which hinder the achievement of gender equality and sustainable development. This study employs a qualitative research method, specifically a case study approach, in North Gorontalo Regency, one of Indonesia's 3T regions. Data collection in this study was carried out through in-depth interviews, observation and document analysis. The results of this study show that inclusive and tailored women's empowerment strategies to local challenges can increase women's access to education, health and economic opportunities and strengthen their participation in decision-making. In addition, the use of digital technology has great potential in accelerating the empowerment process, although there are still infrastructure constraints. A more targeted and sustainable empowerment strategy is needed to promote gender equality and accelerate the achievement of the SDGs in the 3T region.